Character Capacity Building Pramuka melalui Aksi Tanam Mangrove untuk Peningkatan Kualitas Ekosistem di Teluk Pangpang - Roza, Prima; Adhitama, Gregorius Prasetyo; Simarmata, Nirmawana; Hidayat, Esa Fajar (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Pramuka is a scouting movement that teaches many values as the basis for building the character of Indonesia's best human resources. Quality human resources are human capital for developing the nation The scout movement's efforts are primarily concerned with environmental and societal issues. However, there is currently a drop in scouts' interest in activities that involve direct interaction with nature as a result of the younger generation's preoccupation with digital technology, particularly social media. This community service activity from the Institut Teknologi Bandung intends to provide a solution to the worry of diminishing interest in scouting by undertaking mangrove planting activities, which are expected to develop awareness and motivation in scouts to return to enjoying nature-based activities, while building the character of Scouts in their search for identity as a young generation of Indonesia. Mangrove planting activities are carried out with the enforcement scouts of SMK Darul 'Ulum and other community members in the Essential Economic Zone, Wringinputih village, Teluk Pangpang, Banyuwangi, because the sustainability of the mangrove forest ecosystem also requires attention. This activity is expected to increase the interest of Scouts to return to nature, and love the environment, while having an impact on improving the quality of life and welfare of the community.